THE LAWS OF HARMONIZATION IN ARCHITECTURE ACCORDING TO THE THEORY OF M. S. BULATOV (Conferencea, 2022)
This article discusses the laws of harmonization, composition, as well as the design theory of Medieval Islamic architecture. On the example of Khanak Ahmed Yassavi, the canons of geometric harmonization compiled by M. S. Bulatov are studied.